A new simple approach to estimation of membrane capacitance from current responses to voltage clamp steps. (November 2020) - Šimurda, Jiří; Šimurdová, Milena; Švecová, Olga
Abstract: A variety of techniques of cell capacitance measurement have been proposed and applied in cellular electrophysiology. They are mostly based on the evaluation of membrane current responses to small changes in the membrane voltage. One of the currently used approaches applies the least-squares fit of an exponential current decay in response to voltage clamped rectangular pulses. In this study, we propose an alternative simpler approach to evaluation of the exponential parts in the current responses to square wave stimulation and present preliminary results of membrane capacitance evaluation. It is based on the property of the exponential function that has not yet been used to measure membrane capacitance. The time constant and the asymptote of the exponential waveform are unambiguously determined by the values read at three points separated by a constant time interval. In order to minimize the effect of noise and deviations from the exponential waveform, the triplet of points is designed to slide along the time axis. The results of the proposed approach and those previously evaluated by the least squares method are comparable. The method described may be advantageous for continuously recording changes in membrane capacitance. Highlights: A new computer based approach to assessment of cell membrane capacitance was proposed. The parameters of exponential waveform are determined from current values read at three time instants. The triplet is sliding along the time line and the calculated parameters are averaged. Based on simpler calculations, the proposed approach provides much faster results comparable to the least squares method.